U-TRAFMAN: Unmanned traffic management simulator - Jesús Jover; Rafael Casado; Aurelio Bermúdez (SoftwareX)
U-TRAFMAN is a software platform created for simulating scenarios where unmanned traffic management (UTM) is needed, such as U-space. Specifically, the tool allows for the development and evaluation of future services for UTM, the design and verification of aircraft control software, and the collection of data and telemetry for subsequent analysis. The platform is built on the ROS ecosystem, integrating Gazebo and Matlab with the aim of providing a realistic environment with a wide and extensible variety of features and functionalities.